Degradación de las tierras por usos agrícolas intensivos en la Sabana Estacional del Sector Tillavá - los Kioscos en Puerto Gaitán Meta, Colombia (2023)
Eng: The analysis of the land globalization process in Latin America during the period 1950-2019 allowed the identification of countries that have the greatest problems of soil degradation due to the expansion of areas destined for intensive agriculture, whose lands were called savannahs. natural since the fifties. A comparative analysis was made between degraded lands in the savannahs of Brazil, Argentina and Colombia (Tillavá - Los Kioscos sector) in which biophysical and social similarities and differences were identified. For this, documents were reviewed, surveys and free interviews were carried out, in addition, experts in soil degradation from Latin American countries who were aware of the effects of the change of use in their savannah lands were consulted, who shared the advances related to the study. from degradation caused by intensive agricultural use. To understand the problem, the determining characteristics of lands degraded by the establishment of intensive agricultural uses in Latin American countries were identified; Subsequently, the tensions and conflicts associated with the occupation and use of land during the period 1950-2019 in the study sector in the Colombian seasonal savannah were analyzed. Finally, the degraded lands in Latin America due to the implementation of intensive agricultural uses were compared with those of the seasonal savannah of Colombia and the advances associated with the globalization process in these lands. It is concluded that in the lands of the Tillavá - Los Kioscos sector, the processes of territorialization, deterritorialization and re-territorialization were developed, marked by a paradigm shift in the way of defining the aptitude for use of these lands. The presence of induced land degradation caused by intensive agricultural uses was corroborated, which is related to a predatory globalization model applied in Latin America under a continuous procedure in which the conflicts that occurred in Brazil and Argentina are repeated. This pattern of use coincides with the global project based on agro-industrial ventures that use land as crop blocks assigned by global demand. Through the construction of collective knowledge, a technical instrument was proposed that will allow anticipating the consequences of establishing intensive crops in the natural savannah, which considers the susceptibility to degradation of these lands.